DEMERSAL FISHING ANALYSIS OF KUPANG BAY - Mosse, J. W.; Hutubessy, B. G. (Marine Research in Indonesia, 2006)
Study on demersal fish in Kupang bay was carried for 6 months, from July 2002 to December 2002. Sampling was conducted twice a month at the ten-selected locations within the bay using different fishing gears such as gill net, bottom logline, hand line and traps. Fishes caught were stored in a icebox and transferred to the laboratory of the Fisheries Faculty of Artha Wacana Christian University, Kupang for further identification. Similarity index of fish species of the study sites was analyzed using non-metric multidimensional scaling (nMDS) of the matrix Bray Curtis similarity. A computer program PRIMER was used to perform the analysis. The result shows that there are 56 species (total catch 890 fishes) found during this study and their similarity index revealed three groups of study sites. Interestingly, it seems that these species remained to have some strong association with the existing ecosystem. Â